2(5-x)=5(x+3)

Simple and best practice solution for 2(5-x)=5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5-x)=5(x+3) equation:


Simplifying
2(5 + -1x) = 5(x + 3)
(5 * 2 + -1x * 2) = 5(x + 3)
(10 + -2x) = 5(x + 3)

Reorder the terms:
10 + -2x = 5(3 + x)
10 + -2x = (3 * 5 + x * 5)
10 + -2x = (15 + 5x)

Solving
10 + -2x = 15 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
10 + -2x + -5x = 15 + 5x + -5x

Combine like terms: -2x + -5x = -7x
10 + -7x = 15 + 5x + -5x

Combine like terms: 5x + -5x = 0
10 + -7x = 15 + 0
10 + -7x = 15

Add '-10' to each side of the equation.
10 + -10 + -7x = 15 + -10

Combine like terms: 10 + -10 = 0
0 + -7x = 15 + -10
-7x = 15 + -10

Combine like terms: 15 + -10 = 5
-7x = 5

Divide each side by '-7'.
x = -0.7142857143

Simplifying
x = -0.7142857143

See similar equations:

| 63/3^2(5)(5-3) | | 42-2w=4 | | W/2=32 | | 0.50x+0.15(30)=45.5 | | 4y-26-6y+33= | | 5r-45/20=3r-18/3 | | x/10-7/5=x/5-1 | | b/6+3=-7 | | 4z+11=27 | | (2a+3b-4c)+(a-3b-4c)= | | xy=-49 | | 28=12+r*55/(r+55) | | 7.2=42+3-32 | | 21=12+r*55/(r+55) | | 1/6(x+3)=3x-2(3-x)-8 | | (x-2)*(x+1)=x*x-10 | | 1/3(x-2)=3x-2(x-1)+22/3 | | 12-7x=-6x | | 3/4(3x+1)=4(1-3x)+11 | | 3/2(3x+3)=4(1-2x)+13 | | y=6b+3mx | | 8(2n+3)=6(7n+1)+6 | | x+4/4x=0 | | x^2+2x-12y+25=0 | | w/4-3=8 | | 4m-6=22 | | a/3+5=6 | | 2*9-5= | | 3/4x=1/8 | | 6(3x+2)=17x-18x | | 2*9-5=9+4 | | 2+y/3=5 |

Equations solver categories